Typo-morphological analysis applied to a planned new city: adapted concept and method - Bombo Gonçalves, Izabela (2019)
The Italian School of Urban Morphology deals with concepts and methods developed initially from studies performed in historical cities, characterized by organic and spontaneous occupations. This research questions if the Typo-Morphological analysis, an interpretative approach dedicated to understand the urban form through  transformative processes evidenced in architecture, could be efficient in reading and understanding the urban form of planned new cities, established from a plan that precedes their occupation. In order to answer it, a case study was applied in Maringá-PR, Brazil, a planned new city designed in the 1940s. Using the Italian method, it was possible to delineate in detail the processes of transformation and permanence, evidenced throughout its occupation. The results showed that the Italian method was beneficial for the understanding of its urban form. This research demonstrates that the Typo-Morphological analysis is efficient even in cases where buildings were implanted in a previously established urban layout, expanding the range of coverage of the Italian method and contributing to a better understanding of the development and morphological characteristics of planned new cities.